Irreversibility, endogenous mean reversion, and the investment decision of a foreign firm - Christian Pierdzioch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper derives a valuation formula for the real option of a firm to undertake an irreversible investment in a foreign economy based on the endogenous dynamics of a stochastic macroeconomic framework with sluggish price adjustment. The option valuation formula is implemented to analyze the impact of macroeconomic dynamics on the attraction of an economy for foreign investors.
Keywords: F21; F41; 330; Direktinvestition; Gesamtwirtschaftliche Investitionstheorie; Internationale Markteintrittsstrategie; Sunk Costs; Optionspreistheorie; Monetäre Wechselkurstheorie; Stochastischer Prozess; Theorie